Pengaruh Pemberian Tepung Daun Kersen Terfermentasi Dalam Ransum Terhadap Persentase Karkas Dan Persentase Non Karkas Ayam Kampung Super Umur 10 Minggu - Katrin Xandria Oy Sai; Ni Ketut Etty Suwitari; I Gusti Agus Putra Sanjaya (Fakultas Pertanian, Universitas Warmadewa, 2025)
Super free-range chiken is a cross between native chicken and laying hen that grows faster than ordinary native chicken. Native chicken is very good for farmers to cultivate because of its many advantages. Feed is one of the factors that can affect livestock productivity and to reduce this cost is by utilizing leaves, one of which is kersen leaves. The purpose of this study was to influence the provision of fermented cherry leaf flour in rations on the percentage of carcass and non-carcass percentage of 10-week-old super free range chiken. This study used a Completely Randomized Design (CRD) with 5 treatments and 3 replications. Each replication consisted of 5 chickens so that the number of chickens used was 75. The treatments given were P0 control rations without fermented cherry leaf flour, P1 rations containing 3% fermented cherry leaf flour, P2 rations containing 6% fermented cherry leaf flour, P3 rations containing 9% fermented cherry leaf flour, P4 rations containing 12% fermented cherry leaf flour. The results showed that fermented cherry leaf flour in the ration had no significant effect (P>0.05) on slaughter weight, carcass weight, non-carcass weight, carcass percentage and non-carcass percentage. The best level of fermented cherry leaf flour in the ration was at the 12% level treatment.